Micrometeorite accumulation in the Sør Rondane Mountains of East Antarctica - Goderis, Steven; Ginneken, Matthias van; Soens, Bastien; Debaille, Vinciane; Claeys, Philippe (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites / Hayabusa, Wed. 5 Dec. / Conference hall of the Research/Administration Building (2nd floor) at the JAXA Sagamihara Campus conference object